Ensuring The Right of The Suspect And The Accused For Defense - Valerevich Popenkov, Anton (2021)
Authors study the issues of providing the suspect and the accused with the right for defense in criminal proceedings through the prism of the provisions enshrined in international normative legal acts and the Constitution of the Russian Federation. The relevance of this article is substantiated by the authors by the fact that the consideration of the problems of the procedural status of the suspect and the accused in the criminal case should start with this basic provision of the principle of criminal proceedings, such as ensuring the right for protection to the suspect and the accused under article 16 of the Criminal Procedure Code of the Russian Federation. In the context of the modern legal state and the requirements of the Constitution of the Russian Federation, which establishes the basic rights and freedoms of the person and the citizen. The solution to this problem becomes extremely important in the field of criminal justice, which is inevitably associated with the restriction of the constitutional rights of the individual within the limits allowed by law. In this regard, the problems of ensuring the right of the suspect and the accused to a defense require special attention. Based on the results obtained, the authors conclude that compliance with the guarantees of the right to defense of suspects and accused persons has a significant impact on the domestic and foreign policy image of the Russian Federation, being directly proportional to the legal insinuations of international organizations and attempts to influence the Russian legal system.